Palliative care and advance care planning for pancreas and other cancers - Agarwal, Rajiv; Epstein, Andrew S. (Chinese Clinical Oncology, 2017)
The principles of palliative care are fundamental to support and treat the physical, mental, and psychosocial health of patients living with pancreatic cancer. In addition to its proven advantages to help manage disease-related symptoms, improve accurate illness understanding, and enhance the quality of life and survival outcomes for patients with advanced disease, the inclusion of palliative care principles (whether by a specialist or by the primary oncology team) with standard oncologic care strengthens timely and quality advance care planning (ACP). The primary objective of this review article is to underscore the significant value of palliative care integration and ACP in oncology, including but not limited to care at the end of life, with a particular focus on its relevance to patients with advanced pancreatic cancer.